Distinct features distinguishing IgG4-related disease from multicentric Castleman's disease. Issue 1 (18th July 2017) - Sasaki, Takanori; Akiyama, Mitsuhiro; Kaneko, Yuko; Mori, Takehiko; Yasuoka, Hidekata; Suzuki, Katsuya; Yamaoka, Kunihiro; Okamoto, Shinichiro; Takeuchi, Tsutomu
Abstract : Objectives: Differentiating IgG4-related disease (IgG4-RD) from multicentric Castleman's disease (MCD) is challenging because both diseases present high serum IgG4. The objective of this study is to clarify the differences in characteristics and identify a clinically useful approach to differentiate these two diseases. Methods: Forty-five consecutive patients with untreated active IgG4-RD and 33 patients with MCD were included in this study, who visited our institution from January 2000 to August 2016. The clinical and laboratory findings for the patients of the two diseases were compared. Various combinations of the distinctive findings were evaluated to identify the most efficient differentiating features between IgG4-RD and MCD. Results: The levels of serum IgG4 were not different between the two diseases. Orbits, lacrimal glands, salivary glands or pancreas were involved in 88.9% of IgG4-RD cases and only in 3.0% of MCD cases. All MCD cases involved lymph nodes. Atopic history was characteristic for IgG4-RD. The levels of C reactive protein (CRP) with a cut-off of 0.80 mg/dL and IgA with a cut-off of 330 mg/dL were the most distinctive. The combination of 'Orbits, lacrimal glands, salivary glands or pancreas involvement, atopic history, or non-involvement of lymph node' and 'CRP ≤ 0.8 mg/dL or IgA ≤ 330 mg/dL' yielded the probability of 97.8% in IgG4-RD, while that of 3.0 % in patients with MCD. Conclusions: Our study revealed distinct features between IgG4-RD and MCD. Differentiating between the diseases based on those distinct features, including distribution of organ involvement, atopic history, levels of IgA and CRP, was a useful approach.